2017
DOI: 10.1016/j.jjcc.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Individualized antiplatelet therapy after drug-eluting stent deployment: Implication of clinical trials of different durations of dual antiplatelet therapy

Abstract: At present, there is consensus that prolonged dual antiplatelet therapy (DAPT) is effective to reduce cardiovascular events at the expense of bleeding complication events. A causal relationship of prolonged DAPT with an increase in mortality remains debatable, however, it appears to be obvious that bleeding complications are associated with an increase in cardiac events. Thus, individualized optimal DAPT duration balancing the risk and benefit of DAPT should be applied. In addition, strategy to minimize bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the present study, major, minor, and bleeding requiring medical attention were evaluated as the primary endpoint. Various studies have suggested the clinical importance of minor bleeding [26]. Genereux et al reported that not only major but minor bleeding events had a clinical impact on 2-year mortality of postdischarge after PCI [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, major, minor, and bleeding requiring medical attention were evaluated as the primary endpoint. Various studies have suggested the clinical importance of minor bleeding [26]. Genereux et al reported that not only major but minor bleeding events had a clinical impact on 2-year mortality of postdischarge after PCI [27].…”
Section: Discussionmentioning
confidence: 99%
“…Due to multicollinearity, we did not include CKD in baseline characteristics of Table 1. The median DAPT duration was 12 months (IQR, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. DAPT was prescribed in over 80% of all patients.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…To date, there has been no consensus on the optimal DAPT duration, although the importance of balancing the risks and benefits of prescribing DAPT after 2nd-DES implantation has been recognized. Therefore, it is imperative to optimize DAPT duration to patients' characteristics [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%